Desejo e Saber: Desejo de Saber nas trilhas de Freud e Freire - Abbade, Rosane Carvalho da Silveira (2020)
The study focuses on the reflection about the multiple interfaces between Education and Psychoanalysis. Thus, the study explored the concept of desire in psychoanalysis, more precisely the desire for knowledge in the field of education. It first approached the field of Psychoanalysis. In this sense, the footsteps of Freud were followed in unraveling the human psyche and in the construction of fundamental concepts for the dialogue with education. We also sought to analyze if the wish for knowledge is a condition for students to become protagonists of their own learning and also if the teacher’s orientation favors this protagonism, through the analysis of the effect of the transfer process, as well as the influence of transition of different types of curriculum (Traditional versus Problem-Based Learning - PBL) in this development. As instrument for data collection, roundtables were used with two groups of teachers and two groups of students from the first year of the medicine courses at both Unifenas campuses of Alfenas and Belo Horizonte. The roundtables addressed topics such as: what it is, what is the best way to learn. What teaching is like, how it is thought that students learn best, and how we could establish a mutual teaching and learning relationship. The desire for knowledge actually proved to have important influence on the student centered learning as well as the process of transfer between teachers and students. Despite using different teaching methodologies, the courses have not presented significant differences between the students’ and teachers’ perceptions of how the desire is associated to student centered learning